An Anthropological Study Using Van Gennep’s Rites of Passage - Muhammad Nur Fauzan; sapruddin sapruddin; Saifur Rahman (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background: Religious traditions that have developed within Indonesian society reflect the integration of local cultural values with Islamic teachings. One such tradition is the house cleansing ritual in Beringin Jaya Village, Baebunta Selatan Sub-district, Luwu Utara Regency, which is understood as a spiritual means to ward off misfortune, dispel negative energy, and seek blessings. This phenomenon demonstrates how the Qur’an is brought to life in daily practices, making it relevant to be examined through the Living Qur’an approach. Aims: This study aims to analyze the process of traditional house cleaning based on Arnold Van Gennep's rites of passage theory and describe the community's perceptions of the meaning and function of this tradition in their spiritual and social lives. Methods: The study employs a qualitative method with a field research design. Primary data was collected through observation, interviews with six key informants, and documentation, while secondary data was obtained from relevant literature. Data validity was ensured through triangulation techniques, and analysis was conducted using a descriptive-analytical approach, linking the findings to Van Gennep's theory. Result: The results of the study indicate that the traditional house cleansing ritual is divided into three stages: separation, transition, and incorporation. Reciting verses from the Qur'an, such as Surah al-Fātiḥah, Ayat al-Kursi, Surah Al-Falaq, and An-Nas, serves as a means of purifying the house, warding off evil, and calming the soul. The community's perception of this tradition is very positive, as it is believed to revitalize the house, strengthen social bonds, and foster spiritual peace. Conclusion: The results of the study indicate that the traditional house cleansing ritual is divided into three stages, namely separation, transition, and incorporation. Reciting verses from the Qur’an, such as Surah al-Fātiḥah, Ayat al-Kursi, Surah Al-Falaq, and An-Nas, serves as a means of purifying the house, warding off evil, and calming the soul. The community’s perception of this tradition is very positive, as it is believed to revitalize the house, strengthen social bonds, and foster spiritual peace.